Expression of notch signaling genes in putative bladder cancer stem cells - Thirumorthy, Arcana (2017)
Notch signalling is a canonical pathway that is involved in the regulation of stem cell self-renewal and proliferation. This pathway is also involved in the regulation of other cellular processes such as differentiation and apoptosis. Hence, aberrant activation of this pathway is often linked to tumourigenesis. However, the role it plays varies in different cancers. Emerging data has shown that NOTCH1 receptor mutation has a tumour suppressive role in bladder cancer. However, a recent study has shown that not all Notch receptors play a tumour suppressive role. For example, NOTCH2 receptor mutation has an oncogenic role in bladder cancer. Nevertheless, the role of Notch signalling in putative bladder cancer stem cells (CSCs) remains poorly understood. Hence, the main aim of this study was to characterise the expression of Notch signalling associated genes in putative bladder CSCs. To achieve this objective, the putative bladder CSCs were selectively grown as spheroids from four different bladder cancer cell lines (RT112 and SW780 - minimally invasive bladder cancer cells; EJ28 and 5637 - highly invasive bladder cancer cells) in three dimensional (3D)-culture conditions using ultra-low attachment plates. The culture media was optimised for each cell line to allow for spheroid formation. The selectively grown spheroid cells expressed higher level of most commonly studied genes for characterisation of CSCs’ stemness property such as SOX2, NANOG and OCT4 which is in support of the potential stem-like properties of these cells. Analysis of surface markers that are associated with stem cells (CD44, CD49f and CD133) via flow cytometry showed that the expression levels of these markers in the monolayer and spheroid cells were variable, suggesting heterogeneity in the expression signatures of these cells. The expression of Notch signalling associated genes such as NOTCH1-4, HES1, and DUSP1 were also analysed in the spheroid cells using QRT-PCR. All the six Notch signalling genes analysed are genes which has either an oncogenic or tumour suppressive role in cancer cells besides having role in proliferation of CSCs from different cancer types. The expression level of NOTCH2 and HES1 gene was significantly higher in the spheroid cells suggesting that these could be the candidate genes which can be further explored to study putative bladder CSCs. Finally the effect of a gamma-secretase inhibitor, GSI-34, on spheroid cell formation was investigated. GSI-34 is a small molecule inhibitor which had been shown to inhibit cleavage of the gamma-secretase enzyme thus preventing activation of the Notch signalling pathway. In this study, GSI-34 was able to inhibit and reduce the formation and growth of spheroid; albeit there was variation in response across the different spheroids. This study sets the stage for future studies to discover the exact role and mechanism on how Notch pathway regulates the proliferation of bladder cancer stem cells.